Analisis Syariah Marketing Terhadap Pelaksanaan Pemasaran Sabun Multibeauty - Dhuwi Puspita Sari; Yunaita Rahmawati (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
This study aims to determine how the Sharia Marketing Analysis of the Marketing Implementation of Multibeauty Soap. Based on the theory of Sharia marketing, according to Hermawan Kertajaya and Muhammad Syakir Sula, four characteristics of Sharia marketing indicators can be used as a guide for marketers. However, not all indicators of the characteristics of Sharia marketing can be met by marketers. As happened at Alfi Store, there is an injustice in the marketing of multibeauty soap, namely the unequal cutting of soap. However, behind this problem, sales of Multibeauty soap in one-eighth pieces are increasing and attracting consumers. The results of this study indicate that: (1) The implementation of Multibeauty soap marketing based on sharia marketing analysis in general is by the theory. However, some could be more optimal. (2) The impact of implementing Multibeauty soap marketing based on the Sharia marketing analysis felt by Alfi Store, seen from an internal business perspective, explains that Multibeauty soap is by customer specifications. The economic price and a million benefits are one of the advantages of this product. The learning and growth perspective explains that business owners continue to improve their performance by regularly conducting sharing and seminars with other business partners. The customer perspective explains that consumers of Multibeauty soap feel satisfied. The financial perspective explains that consumers make repeat orders, which increases the number of sales of Multibeauty soap by one-eighth piece. (3) The factors that affect the level of sales of Multibeauty soap are affordable prices, best quality, distribution channels, and good service.